Place and belonging in America - Jacobson, David, 1959- (Johns Hopkins University Press, 2002)
"How did the American people come to develop a moral association with this land, such that their very experience of nationhood was rooted in, and their republican virtues depended upon, that land? And what is happening now as the exclusivity of that moral linkage between people and land becomes ever more attenuated? In Place and Belonging in America, David Jacobson addresses the evolving relationship between geography and citizenship in the United States since the nation's origins."--Jacket